LOCAL COMMUNITY PARTICIPATION IN ECOTOURISM DEVELOPMENT: THE CASE OF SUMBERWANGI HAMLET DESTINATION, EAST JAVA, INDONESIA - Giriwati, Novi Sunu Sri; Hawa, La Choviya; Pamungkas, Sigmawan Tri; Iyati, Wasiska; Hidayat, A R Taufiq (PEOPLE: International Journal of Social Sciences, 2019)
The Mountainous area of Arjuno, located in east Java with its beautiful natural scenery and cultural historical situs has significant potential for tourism development. In the slopes of Mount Arjuno, there is one traditional settlement, Sumberwangi hamlet. It has nice view and cool climate that is typical of the the highlands. This hamlet also produce Javanese coffee such as a Arabica and Robusta. Since 2015 the forest manage by University of Brawijaya (UB) under supervised of Ministry of Environment. Besides its potential, Sumberwangi hamlet has possibility of strong wind attack. This study examines the level and model of local community participation in ecotourism facility development. The form of empowerment was determined for every step of destination planning. The data were collected using documentation and interview. The result of the study indicates that the community involvement is at passive level. The form of empowerment was determined for every step of destination planning. The model of community participation in Sumberwangi is community empowerment in the project. The citizen is involved in three area of development. In the planning stage, community is given the information and identify the potential of Sumberwangi together with the companion. In the development stage, community is involved in master planning and tourist accommodation design. In the final stages, community is involved in program evaluation together with the research team. Ecotourism is expected to be the best development model as it empowering local community whilst conserving the nature and local wisdom. This study hopefully could give significant contribution for ecotourism development in Sumberwangi hamlet, UB forest.